BUILDING CHILDREN'S INDEPENDENCE THROUGH PARENTS - M. Ahim Sulthan Nuruddaroini; Syamsiah; Husin; Abdul Rashid bin Abdul Aziz (International Forum of Researchers and Lecturers, 2022)
Early childhood is also known as the golden age, in which the potential and abilities of the physical, cognitive, language, artistic, social-emotional, moral, religious, self-concept, self-discipline and independence develop. Therefore it is important if from an early age it is necessary to instill the value of independence in children. One of the factors that can influence the process of developing independence in children is parenting style. This study aims to determine the parenting style of parents in building children's independence, because the role of parents is very important in building independence in children. The research method used is library research or library research. The results of this study are through parenting parents are able to build children's independence, including in applying habits to children. The activities in building independence in children include, 1) Physical activity, namely getting children to do activities independently, for example brushing their teeth, eating, wearing their own clothes 2) Fostering a sense of self-confidence 3) Building a sense of responsibility such as training children to complete school assignments. 4) Getting used to disciplined attitudes such as getting disciplined children to come to school and 5) Socializing by giving children the opportunity to interact with their friends who were initially shy to become brave. 6) controlling emotions by teaching children to be patient when their wishes are not fulfilled. wearing own clothes 2) Growing self-confidence 3) Building a sense of responsibility such as training children to complete school assignments. 4) Getting used to disciplined attitudes such as getting disciplined children to come to school and 5) Socializing by giving children the opportunity to interact with their friends who were initially shy to become brave. 6) controlling emotions by teaching children to be patient when their wishes are not fulfilled. wearing own clothes 2) Growing self-confidence 3) Building a sense of responsibility such as training children to complete school assignments. 4) Getting used to disciplined attitudes such as getting disciplined children to come to school and 5) Socializing by giving children the opportunity to interact with their friends who were initially shy to become brave. 6) controlling emotions by teaching children to be patient when their wishes are not fulfilled.